2016
DOI: 10.1063/1.4962474
|View full text |Cite
|
Sign up to set email alerts
|

Transparent electromagnetic shielding enclosure with CVD graphene

Abstract: Cavity resonant modes of shielding enclosure for housing electronic circuits may cause electromagnetic interference (EMI). Here, we present an effective approach by using graphene to suppress unwanted resonant modes while maintaining good transparency to visible light. The structure consists of graphene sheet on quartz substrate attached to the shielding enclosure made from indium tin oxide. We experimentally demonstrate that the proposed approach can lead to good absorption of microwave waves at a wide freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…According to the measured electromagnetic parameters, the transmission line theory was used to calculate and analyze their reflection loss. The formulas are as follows [8]:…”
Section: Characterization and Testingmentioning
confidence: 99%
“…According to the measured electromagnetic parameters, the transmission line theory was used to calculate and analyze their reflection loss. The formulas are as follows [8]:…”
Section: Characterization and Testingmentioning
confidence: 99%
“…Apart from the application for attenuators, absorbers and antennas, the CVD-grown graphene can also be used in EMI shielding or the beam configuration field. In 2016, Wu et al proposed a transparent electromagnetic shielding enclosure based on CVD-grown graphene [31]. It can be observed from Figure 10 that the monolayer graphene with the surface impedance of 500 V/□ on the quartz substrate is attached to an enclosure made of indium tin oxide (ITO).…”
Section: Other Devices Based On Cvd-grown Graphenementioning
confidence: 99%
“…24 Zhao et al designed an optically transparent shielding enclosure by integrating indium tin oxide with graphene/quartz substrates, which effectively suppresses the cavity-resonant modes, and the shielding enclosure may cause EMI. 25 Wen et al reported high-efficiency EMI shielding of light-weight RGOs at elevated temperatures. 26 Cao et al found that ultrathin and lightweight graphene composites exhibit high-efficiency microwave absorption at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al investigated the EM interference (EMI) shielding performance of multilayer graphene (without doping)/polyethylene terephthalate (PET) structure at 18–26.5 GHz . Zhao et al designed an optically transparent shielding enclosure by integrating indium tin oxide with graphene/quartz substrates, which effectively suppresses the cavity-resonant modes, and the shielding enclosure may cause EMI . Wen et al reported high-efficiency EMI shielding of light-weight RGOs at elevated temperatures .…”
Section: Introductionmentioning
confidence: 99%